THE CHARACTERISTICS OF BLOOD LIPIDS OF MENOPAUSAL WOMEN WITH THE COMPENSATED HYPOTHYROIDISM WHICH RESULTS FROM AUTOIMMUNE THYROIDITIS - Yu. A. Malyshenko; O. D. Rymar; M. V. Ivanova; L. V. Shcherbakova; S. F. Zhinchyk (Бюллетень сибирской медицины, 2014)
Purpose: to study the lipid profile, including of non-high-density lipoproteins cholesterol (non-HDL-C), in postmenopausal women with compensated hypothyroidism. The causes of hypothyroidism included Hashimoto thyroiditis.45 women with hypothyroidism participated in the study (mean ± sd, age (57.4 ± 7.7) years, disease duration (8.0 ± 6.4) years, the duration of postmenopause (6.4 ± 3.5) years). The mean dose of L-T4 (84.3 ± 28.5) μg/d. The control group – 85 women (mean ± sd, age (58.4 ± 5.4) years) no abnormalities of the thyroid gland, as well as other chronic diseases, which could have an impact on lipid metabolism.The main and control group were matched for age. Average BMI basic group than in controls: (31.6 ± 3.4) and (28.7 ± 4.6) kg/m2 respectively (p = 0.001). Obtained statistical differences in terms of TSH in the study and control groups: 2.15 and 1,22 mU/L (p = 0.001). Upon reaching euthyrosis against the background of hormone replacement therapy with thyroid hormones do not reach the target total cholesterol (TC), low density lipoproteins cholesterol (LDL-C): 5.81 ± 1.14, 3.67 ± 1.06 respectively.We obtain lower high-density lipoproteins cholesterol (HDL-C) levels in women with drug euthyroidism compared with the control group. Do not get the difference in the values non-HDL-C in the groups studied. In postmenopausal women with compensated hypothyroidism is defined negative correlation ATTPO with HDL-C. Mean values of blood TC, non-HDL-C, LDL-C levels in the groups exceed the optimal ones.